2008
DOI: 10.1002/cphc.200700609
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Energetically Activated Cumulenes—From Allene (H2CCCH2) to Hexapentaene (H2CCCCCCH2)

Abstract: During the last decade, experimental and theoretical studies on the unimolecular decomposition of cumulenes (H(2)C(n)H(2)) from propadiene (H(2)CCCH(2)) to hexapentaene (H(2)CCCCCCH(2)) have received considerable attention due to the importance of these carbon-bearing molecules in combustion flames, chemical vapor deposition processes, atmospheric chemistry, and the chemistry of the interstellar medium. Cumulenes and their substituted counterparts also have significant technical potential as elements for molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 151 publications
1
69
0
Order By: Relevance
“…Cumulenes consist of linear sp‐hybridized carbon atoms in a contiguous sequence of double bonds (vs. polyynes composed of alternating single and triple bonds; Figure ). In addition to potentially serving as model compounds for carbyne, both theory and experiment predict a number of fascinating properties for these compounds which could give rise to applications in nanoelectronic or spintronic devices, molecular wires, nonlinear optics, and others . Carbo ‐mers are compounds where molecular symmetry is retained while one cumulenic unit (=C=C=) is inserted into each −C−C− single bond and one acetylenic unit (−C≡C−) is inserted into each −C=C− bond of a CPH .…”
Section: Snii‐mediated Reduction Of Diolsmentioning
confidence: 99%
“…Cumulenes consist of linear sp‐hybridized carbon atoms in a contiguous sequence of double bonds (vs. polyynes composed of alternating single and triple bonds; Figure ). In addition to potentially serving as model compounds for carbyne, both theory and experiment predict a number of fascinating properties for these compounds which could give rise to applications in nanoelectronic or spintronic devices, molecular wires, nonlinear optics, and others . Carbo ‐mers are compounds where molecular symmetry is retained while one cumulenic unit (=C=C=) is inserted into each −C−C− single bond and one acetylenic unit (−C≡C−) is inserted into each −C=C− bond of a CPH .…”
Section: Snii‐mediated Reduction Of Diolsmentioning
confidence: 99%
“…We use both even-numbered and odd-numbered clusters since, for any given structure of the anchoring sites, the parity of the carbon atoms plays a crucial role in the electronic structure of the chains [38,39] (e.g., on the orientation of the p orbitals of double C-C bonds). In principle, two isomeric forms of carbyne are possible.…”
Section: O 2 Adsorption On Supported Carbon Chainsmentioning
confidence: 99%
“…24 Cumulenes find major application in molecular machines (nanomechanics), molecular wires (nano-electronics), nonlinear optics, and molecular sensors due to their unique electronic structures. 25 It is found that among all conjugated oligomers, cumulene wires with odd number of carbon atoms show the highest conductance with metallic-like ballistic transport behavior. 26 1 2 3 1 2 3 4 5 1 2 3 4 5 6 7 1 2 3 1 2 3 4 5 1 2 3 4 5 6 7 1 2 3 1 2 3 4 5 1 2 3 4 5 6 7 Series 1 Series 2 -indicates the number of carbon atoms in coupler).…”
Section: Introductionmentioning
confidence: 99%